ANA LISIS ISI LAMBUNG PENSI (Corbicula moltkiana) YANG TERDAPAT DI DANAU MANINJAU - Desyiska, Desyiska; Nurhadi, Nurhadi; Abizar, Abizar (Pendidikan Biologi, 2013)
Maninjau Lake is one lake in West Sumatra and ample potential. Maninjau currently used for various activities, such as fisheries, tourism, Hydroelectric Power Plant (HEPP), Shower Wash latrine (toilet) and disposal of household waste. The last few years the population activity in the body and on the edge of the lake has increased as fish farming system with floating nets. Activities around the lake residents and lake bodies, suspected to cause impaired. Her balance of the lake ecosystem which affect lake biota. such as art shows moltkiana Corbicula. The presence of Corbicula pensi moltkiana in Maninjau can be used as an additional income for the communities around the lake. But according to the day pensi harvester Corbicula moltkiana hard to come by. In connection with that the authors have conducted a study with the aim of knowing the natural food of pensi. The study was conducted in May 2012 with a descriptive survey method by setting the four stations based activities alongside a lake and the lake body Muko-Muko as a tourism spot (Station I), Forage Fish farming cages Rabaa (Station II), Bayur Agricultural area (Station III ), and community activities Maninjau quite high (station IV). In this research pensi pensi used is larger than 15mm. On each - each station established 3 sampling points. Pensi samples taken 6 tails of each station. At each sampling point taken 2 pensi tail. Laboratory sample identification STKIP PGRI West Sumatra. Parameters measured were relative density and relative frequency as well as water quality parameters measured were temperature and pH. From the research found 14 types of natural foods pensi belonging to class